Leadership in Organizational Development - Lisda L Asi (Journal of International Conference Proceedings (JICP), 2019)
The fundamental problem that calls for the attention and thought of company leaders is how to develop and make changes to organizational adjustments, so that they are better able to resolve and determine direction in an environment that is constantly changing where the organization operates. In facing this changing environment. Leadership is an important part of management, although not entirely, for example, managers must plan and organize, but the main role of leadership is to influence others to achieve the goals set. This is evidence that the leader may be a weak manager if the planning is bad which causes the group to go in the wrong direction. As a result, although they can move the work team, they do not go towards achieving organizational goals. Leadership is related to the process which affects people so that they reach the target in certain circumstances. Organizational leaders strive to organize and carry out organizational operations well. This paper discusses how to prepare leadership in organizational development to face a dynamic and constantly changing environment.